PENERAPAN METODE PERMAINAN BISIK BERANTAI TERHADAP KETERAMPILAN BERBICARA SISWA KELAS IV SDN RANDUGARUT - Madaliyah Izah Mansyur (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
This research originated from observations that have been made in Class IV of Randugarut State Elementary School, that students' speaking skills are still lacking. This study aims to determine the application of the whispering chain game method to the speaking skills of fourth grade students of Randugarut State Elementary School. This type of research is quantitative research with experimental research type. The population in this study were all fourth grade students of Randugarut State Elementary School, totaling 23 students. The sampling technique uses purposive sampling Data collection was done through observation method and test method. The results of the research that has been carried out show that the use of the whispering chain game method affects the speaking skills of grade IV students of Randugarut State Elementary School, this is evidenced by the increase in the results of students' speaking skills in the experimental class. And there is a significant effect on the application of the chain sentence game method on the speaking skills of class students.